PENENTUAN UMUR EKONOMI WHEEL LOADER VOLVO L220G MENGGUNAKAN MINIMUM COST METHOD - Krismantoro, Daniel Dani Wahyu; Ghalib, Saladin; Rasyidi, Rasyidi (JURNAL BISNIS DAN PEMBANGUNAN, 2020)
Daniel Dani Wahyu Krismantoro, D2A215003, 2015. Determination of the Economic Life of the Volvo L220G Wheel Loader Using the Minimum Cost Method, under the guidance of Saladin Ghalib and Rasyidi. This study aims to, 1) Establish a regression model of equipment age (X) with the cost of repairs and maintenance (Y), 2) Determine the economic life of the equipment with the Minimum Cost Method, and 3) Determine significant factors that influence the determination of economic life using sensitivity analysis and Monte Carlo simulation. The population was taken from 5-unit Volvo L220G Wheel Loader that has been operating in Jetty-R coal port, Kab. Tapin, South Kalimantan. Data collection uses interviews and observation method. The researches data was taken in the span of 2014 - 2018 with the equipment life 15,000 - 18,500 working hours.The results obtained, 1) The cost model follows the equation Y = 1752.6 + 0.2046X + 0.0002X ^ 2 where X is the age of the equipment (Independent Variable) and Y is the maintenance cost (Variable Cost). 2) Economic life is calculated by using the Minimum Cost Method which occurs in the fourth year (working hours 13,537.84). 3) the factors that most influence the ownership and operational costs are the cost of purchasing fuel, the cost of ownership and the cost of repairs and maintenance. Keywords: Economic Life, Minimum Cost Method, Wheel Loader Volvo L220G